2015
DOI: 10.1123/jab.2014-0188
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Trunk Axial Kinematics to Poststrike Ball Velocity During Maximal Instep Soccer Kicking

Abstract: To date, biomechanical analyses of soccer kicking have focused predominantly on lower-extremity motions, with little emphasis on the trunk and upper body. The purpose of this study was to evaluate differences in trunk axial kinematics between novice (n = 10) and skilled (n = 10) participants, as well as to establish the relationship of trunk axial motion and sagittal plane thigh rotation to poststrike ball velocity. Three-dimensional body segmental motion data were captured using high-resolution motion analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
0
11
1
Order By: Relevance
“…parameters, such as ball release velocity during a handball throw, 3 soccer instep kick, 4 field hockey drag flick, 5 golf swing, 6 tennis serve, 7 and cricket fast bowling 8 or power output during flat-water kayak paddling. 9 During dynamic sports motions, trunk motion is also associated with the risk of lower limb, upper limb, and spinal injuries.…”
mentioning
confidence: 99%
“…parameters, such as ball release velocity during a handball throw, 3 soccer instep kick, 4 field hockey drag flick, 5 golf swing, 6 tennis serve, 7 and cricket fast bowling 8 or power output during flat-water kayak paddling. 9 During dynamic sports motions, trunk motion is also associated with the risk of lower limb, upper limb, and spinal injuries.…”
mentioning
confidence: 99%
“…However, this relationship between the tension arc and kick distance was not seen in the current study. Recently, Fullenkamp et al (2015) showed the importance of the trunk rotation in attaining ball velocity. While no relationship was shown in the current study between X-factor and kick distance, the significant relationship between the X-factor and kick accuracy was presented.…”
Section: Kick Distance and The Kinetic Chainmentioning
confidence: 99%
“…While no relationship was shown in the current study between X-factor and kick distance, the significant relationship between the X-factor and kick accuracy was presented. The kinematic variable X-factor, the separation of the torso relative to the pelvis, was similar to the trunk axial rotation used in the Fullenkamp et al (2015) study. Surprisingly, the back flexion and the lateral bend angle at ball contact had no significant relationship with either kick distance or kick accuracy.…”
Section: Kick Distance and The Kinetic Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a limitation of these findings is that they consider the kick leg independent from the rest of the body (Lees et al, 2010). More recent evidence suggests that the support leg, pelvis and torso also all contribute to kicking performance (Augustus et al, 2017;Fullenkamp et al, 2015;Inoue et al, 2014;Naito et al, 2010). Pelvis rotations about the support leg may precede kick leg sequencing (Inoue et al, 2014;Lees et al, 2009), and concentric work performed at the support knee (Augustus et al, 2017) and torso (Naito et al, 2010) may serve to extend the kicking knee later in the downswing.…”
Section: Introductionmentioning
confidence: 99%